Material and human resources for neonatal resuscitation in public maternity hospitals in Brazilian state capitals - Almeida, Maria Fernanda Branco de; Guinsburg, Ruth; Costa, José Orleans da; Anchieta, Lêni Márcia; Freire, Lincoln Marcelo Silveira (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: In 2002, the early neonatal mortality rate in Brazil was 12.42 per thousand live births. Perinatal asphyxia was the greatest cause of neonatal death (about 23%). This study aimed to evaluate the availability of the resources required for neonatal resuscitation in delivery rooms of public hospitals in Brazilian state capitals. DESIGN AND SETTING: Multicenter cross-sectional study involving 36 hospitals in 20 Brazilian state capitals in June 2003. METHODS: Each Brazilian region was represented by 1-4% of its live births. A local coordinator collected data regarding physical infrastructure, supplies and professionals available for neonatal resuscitation in the delivery room. The information was analyzed using the Statistical Package for the Social Sciences, version 10. RESULTS: Among the 36 hospitals, 89% were referral centers for high-risk pregnancies. Each institution had a monthly mean of 365 live births (3% < 1,500 g and 15% < 2,500 g). The 36 hospitals had 125 resuscitation tables (3-4 per hospital), all with overhead radiant heat, oxygen and vacuum sources. Appropriate equipment for pulmonary ventilation was available for more than 90% of the 125 resuscitation tables. On average, one pediatrician, three nurses and fi ve nursing assistants per shift worked in the delivery rooms of each institution. Out of the 874 pediatricians and 1,037 nursing personnel that worked in the delivery rooms of the 36 hospitals, 94% and 22%, respectively, were trained in neonatal resuscitation. CONCLUSIONS: The main public maternity hospitals in Brazilian state capitals have the resources to resuscitate neonates at birth.